Perlindungan Hukum Karya Desain Digital Yang Dijual Pada Platform E-Commerce - Afif, Ega Haidar; Marsitiningsih, Marsitiningsih (Fakultas Hukum Universitas Islam Batik Surakarta, 2024)
With the development of digital technology, creators can now use e-commerce platforms to sell digital design works. The ease of access and digital nature of these design works raises concerns about potential copyright infringement. Digital intellectual property, such as logos, illustrations and icons must be protected. The research aims to find out and examine the legal protection of digital design works so as not to be misused by other parties on digital e-commerce platforms and the legal efforts of copyright holders of digital designs to be protected. The research was conducted using normative method. The results show that digital designs sold on e-commerce platforms get protection against ownership of intellectual property rights both from economic rights and moral rights as stated in Article 8 to article 19 and articles 21 and 22 of Law Number 28 of 2014 concerning Copyright and article 25 of Law Number 19 of 2016 amending Law Number 11 of 2008 concerning ITE. Preventive efforts to protect a digital design creation can be done by inserting a watermark on the digital design and registering the digital design copyright at the Directorate General of Intellectual Property. E-commerce platforms can act decisively against individuals who infringe copyright by giving warnings, imposing penalties, removing and stopping products to closing the accounts of copyright infringers. Repressive efforts to resolve digital design copyright disputes can be resolved through temporary injunctions, civil remedies, criminal remedies and arbitration.